2007
DOI: 10.1016/j.yjmcc.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in myocardial infarction and rupture

Abstract: Although myocardial rupture occurs in a relatively low percentage (2-4%) of cases of acute myocardial infarction (MI), it is associated with an extremely high mortality rate due to cardiogenic shock (up to 90% in cases of free wall rupture and 50% of cases involving septal rupture), and it accounts for up to 25% of in-hospital death [1]. Understanding the molecular mechanisms leading to myocardial rupture therefore represents an important challenge for improving the short term prognosis of MI. In the present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although it is widely accepted that the increase in SBP with advancing age is mostly consistent with the large artery stiffening [ 2 , 4 7 ], there is still no consensus on what are the primary causes of these disorders. Our recent studies show that increased intrinsic stiffness of vascular smooth muscle cells (VSMCs) in aorta is an important contributor to the pathogenesis of aortic stiffening in both aging and hypertension, and that this could be a novel target for future anti-aortic stiffness drug development [ 8 10 ]. However, less is known about molecular regulation involved in the VSMC stiffening in large arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is widely accepted that the increase in SBP with advancing age is mostly consistent with the large artery stiffening [ 2 , 4 7 ], there is still no consensus on what are the primary causes of these disorders. Our recent studies show that increased intrinsic stiffness of vascular smooth muscle cells (VSMCs) in aorta is an important contributor to the pathogenesis of aortic stiffening in both aging and hypertension, and that this could be a novel target for future anti-aortic stiffness drug development [ 8 10 ]. However, less is known about molecular regulation involved in the VSMC stiffening in large arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Rho kinase (Rho-associated coiled-coil-containing protein kinase, hereafter referred to as ROCK) is a serine/threonine protein kinase that contains an N-terminal catalytic kinase domain, which has been identified as one of the effector of the small GTP-binding protein Rho. Although accumulating evidences have demonstrated that the ROCK pathway plays a crucial role in the pathogenesis of hypertension [ 8 , 11 , 12 ], ROCK has not previously been shown to be involved in cellular stiffening of VSMC. Inhibition of ROCK with Y-27632, fasudil or SAR407899 significantly reduced blood pressure in human and animal models of hypertension [ 12 15 ], despite the precise molecular mechanism underling the antihypertensive effect not being fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although lifetime risk estimates for HF are comparable in both sexes, at about 20% ( 4 , 5 ), the biological response to HF precursors is fundamentally different among women and men. For instance, after ischemic myocardial injury, adverse cardiac remodeling is more commonly observed in men than women ( 6 , 7 ). When subjected to pressure or volume overload, female hearts hypertrophy more than male hearts and tend to remodel in a concentric pattern, whereas male hearts more often display an eccentric remodeling pattern ( 8 , 9 , 10 , 11 , 12 , 13 ).…”
mentioning
confidence: 99%
“…A study found in both genders mice, the total collagen amount was similar, but males were more fragile due to a 70% reduction on cross-linked collagen. 24 It was also important to point out that higher mortality rates in women may also be affected by the delay presentation and diagnosis compared to men 25 , and also by other cultural and financial factors, resulting in cases in female resurfaced.…”
Section: Discussionmentioning
confidence: 99%